The Challenge of Rethinking History Education : On Practices, Theories, and Policy. - VanSledright, Bruce (Taylor & Francis, 2010)
A work that is suitable for those looking for a guide to both the theory and practice of what it means to teach historical thinking, to engage in investigative practice with students, and to increase students' capacity to critically read and assess the nature of the complex culture in which they live.